متطلبات تطبيق إعادة هندسة العمليات الإدارية في المؤسسة الاقتصادية دراسة حالة مؤسسة صناعة الكوابل - فرع كوندور- بسكرة - قريشي, محمد; غربال, أحلام (Université de M'sila, 2019)
الملخص هدفت هذه الدراسة إلى التعرف على مستوى توفر متطلبات تطبيق إعادة هندسة العمليات الإدارية بمؤسسة صناعة الكوابل بسكرة، ولتحقيق ذلك تم صياغة فرضية رئيسية متضمنة سبعة فرضيات فرعية، وشملت الدراسة جميع إطارات مؤسسة صناعة الكوابل ببسكرة، وقمنا بتوزيع الاستبانة عليهم جميعا عبر عدة زيارات ميدانية، وأسترد منها (60) إستبانة، وبعد فحصها لم يُستبعد أي منها نظرا لتحقيقها شروط الإجابة الصحيحة. قمنا بإستخدام عدة أساليب إحصائية لتحليل البيانات منها: مقاييس الإحصاء الوصفي (الوسط الحسابي، الإنحراف المعياري)، وإختبار T للعينة الواحدة One Sample T- test...الخ. توصلت الدراسة إلى عدة نتائج أهمها أن مستوى توفر متطلبات إعادة هندسة العمليات الإدارية جاء مرتفعا بدلالة ارتفاع الوسط الحسابي للإجابات (3.968). وعلى ضوء هذه النتائج قمنا بتقديم مجموعة من التوصيات أهمها: على المؤسسة محل الدراسة زيادة الإهتمام بإعادة هندسة العمليات الإدارية بأبعادها المختلفة وضرورة النظر إليها على أنها أحد المداخل الحديثة التي حققت ثورة في عالم الإدارة لمواكبة تغيرات المحيط باستمرار، بهدف الوصول إلى تحسينات جذرية في الأداء. الكلمات المفتاحية: إعادة هندسة العمليات الإدارية، المبادرة، تكنولوجيا المعلومات، السياسات الإدارية، التخطيط الإستراتيجي، التدريب، تنمية مهارات العاملين، والقوانين والتشريعات. Abstract: The purpose of this study is to identify the level of availability of the requirements of the re-engineering of the administrative processes at the Cable Industry company in Biskra. To achieve this, a main hypothesis was formulated including seven sub-hypotheses. The study included all the qualified employees of the Cable Industry company in Biskra, where we gave out the questionnaire to them all through several field visits and we have brought back (60) questionnaires, and after examining them, none of them were excluded due to the fulfillment of the conditions of the correct answer. We have used several statistical methods to analyze data, including descriptive statistical measures (Mean, Standard Deviation), One Sample T- test … etc. The study’s results showed that the level of availability of the re-engineering requirements of the administrative processes was high in terms of the high mean of the answers (3.968). In light of these results, we have made a number of recommendations. The most important of these recommendations are: The institution under study should increase the interest in re-engineering the administrative processes with its different dimensions and the need to view them as one of the modern approaches that have revolutionized the management world to keep pace with the changes in the outside world. Keywords: re-engineering of administrative processes, initiative, information technology, management policies, strategic planning, training, staff development employees, laws and legislation.
Keywords: إعادة هندسة العمليات الادارية ; المبادرة ; السياسات الادارية ; التخطيط الاستراتيجي ; التدريب ; تنمية مهارات العاملين